The contribution of education to the economic growth - Χατζηδήμα, Σταματίνα (SPOUDAI Journal of Economics and Business, 2002)
This paper reviews some of the major theoretical contributions to the literature on growth and education. The discussion is focused on the Greek case. The typical macro growth model is employed in order to examine the effect of the change in schooling on the economic growth. Some conclusions were drawn from the analysis of data available for Greece for the time period 1974-2000. JEL Classification: 21